(–)-Epicatechin Alters Reactive Oxygen and Nitrogen Species Production Independent of Mitochondrial Respiration in Human Vascular Endothelial Cells. (11th January 2022) - Sadler, Daniel G.; Barlow, Jonathan; Draijer, Richard; Jones, Helen; Thijssen, Dick H. J.; Stewart, Claire E.
Abstract : Introduction . Vascular endothelial dysfunction is characterised by lowered nitric oxide (NO) bioavailability, which may be explained by increased production of reactive oxygen species (ROS), mitochondrial dysfunction, and altered cell signalling. (-)-Epicatechin (EPI) has proven effective in the context of vascular endothelial dysfunction, but the underlying mechanisms associated with EPI's effects remain unclear. Objective(s) . Our aim was to investigate whether EPI impacts reactive oxygen and nitrogen species (RONS) production and mitochondrial function of human vascular endothelial cells (HUVECs). We hypothesised that EPI would attenuate ROS production, increase NO bioavailability, and enhance indices of mitochondrial function. Methods . HUVECs were treated with EPI (0-20 μ M) for up to 48 h. Mitochondrial and cellular ROS were measured in the absence and presence of antimycin A (AA), an inhibitor of the mitochondrial electron transport protein complex III, favouring ROS production. Genes associated with mitochondrial remodelling and the antioxidant response were quantified by RT-qPCR. Mitochondrial bioenergetics were assessed by respirometry and signalling responses determined by western blotting. Results . Mitochondrial superoxide production without AA was increased 32% and decreased 53% after 5 and 10 μ M EPI treatment vs. CTRL (P < 0.001 ). With AA, only 10 μ M EPI increased mitochondrial superoxide production vs. CTRL (25%, P < 0.001 ). NO bioavailability was increased by 45% with 10 μ M EPI vs. CTRL (P = 0.010 ). However, EPI did not impact mitochondrial respiration. NRF2 mRNA expression was increased 1.5- and 1.6-fold with 5 and 10 μ M EPI over 48 h vs. CTRL (P = 0.015 and P = 0.001, respectively). Finally, EPI transiently enhanced ERK1/2 phosphorylation (2.9 and 3.2-fold over 15 min and 1 h vs. 0 h, respectively; P = 0.035 and P = 0.011 ). Conclusion(s) . EPI dose-dependently alters RONS production of HUVECs but does not impact mitochondrial respiration. The induction of NRF2 mRNA expression with EPI might relate to enhanced ERK1/2 signalling, rather than RONS production. In humans, EPI may improve vascular endothelial dysfunction via alteration of RONS and activation of cell signalling.